Perspectives: The Dance of Love and Fear in the Middle East: An Invitation for Change? - Lavy, Shiri (Middle East Journal of Positive Psychology, 2020)
This pandemic year will be remembered for many things. It has brought worldwide challenges and transformations. In the Middle East/North Africa region, it brought unique winds of change in the geopolitical arena, with the signing of the Abraham Accord between the governments of Israel and the United Arab Emirates. While the relationship continues to mature, there are many opportunities through which greater dialogue and understanding can evolve; more importantly, there is a vital role for regional positive psychologists to play. Across many areas of shared interest, i.e. large youth population, more traditional, religious cultures than those found in the Western countries that are typically studied in positive psychology, a regional research agenda can be formed and jointly pursued. Through such shared endeavors, greater wellbeing for individuals and societies alike can be fostered and promoted, alongside more interpersonal understanding and better working relationships. Positive psychology as a whole can also benefit from the development of such empirical knowledge as it adds to a greater global understanding of wellbeing in diverse cultural contexts.